Life on the podium and out of the closet: LGBTQ+ collegiate wind band conductor’s experiences of (in)dignity in the workplace - Ricker, Mark Evan, Jr. (Kansas State University, 2023)
This narrative study explored the experiences of four collegiate-level LGBTQ+ wind band conductors who have experienced (in)dignity in the workplace and their thoughts on promoting dignity and preventing abuse in the workplace. Informed by a workplace dignity approach, four LGBTQ+ college wind band conductors were interviewed to gain a deeper understanding of the experience of (in)dignity and the navigation of dignity slights and affirmations. Through in-depth, semi-structured interviews, respondents discussed their experiences with (in)dignity, how it relates to gender, sex, and sexuality, how they respond to slights and affirmations of dignity, and potential tactics for promoting dignity and preventing dignity threats. Participants shared stories of their encounters with (in)dignity in their working lives. The analysis of these stories revealed a collective definition of dignity and gave insight into the factors that contribute to dignity slights and affirmations. Discussions with the participants illuminated several opportunities that could lead to a more affirming workplace and hinder dignity slights.
Keywords: Dignity; LGBTQ+; Wind band conductors; College